Technical and Administrative Challenges in Filing Annual Tax Returns by Individual Taxpayers: A Case Study at the Pratama Tax Service Office Cicadas Bandung - Tria Nur Glarty (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The Annual Tax Return (SPT) filing is a crucial obligation for individual taxpayers in Indonesia. However, in practice, various technical and administrative challenges are still encountered. This study aims to identify and understand the obstacles faced by individual taxpayers in the process of filing their Annual Tax Returns, using a case study at the Primary Tax Office (KPP Pratama) Cicadas, Bandung. A descriptive qualitative approach was employed through in-depth interviews with tax officers and analysis of relevant tax policy documents. The findings reveal that technical issues include difficulties accessing the DJP Online system, limited technological proficiency, and problems related to EFIN and Multi-Factor Authentication (MFA). On the administrative side, the challenges involve incomplete supporting documents, lack of understanding of tax regulations, and low compliance awareness. Nevertheless, the Directorate General of Taxes (DJP) has implemented several initiatives such as education through university Tax Centers, the Renjani Tax Volunteer program, and the development of the Coretax system to support more efficient tax reporting. The study recommends innovative communication strategies, enhanced taxpayer literacy, and accelerated digitalization of tax services to improve taxpayer compliance.